Penerapan Gamifikasi Kahoot Dalam Meningkatkan Hasil Belajar Menulis Teks Argumentasi Siswa Kelas IX SMA Negeri 5 Makassar - Paputungan, Dewi P.; Ramly, Ramly; Wahab, Wahab (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to determine the improvement of learning outcomes in writing argumentation texts of SMA Negeri 5 Makassar students by using Kahoot gamification. This research is included in class action research. The data collected in the form of process data, including student activities and student argumentation text learning outcomes through the use of the Kahoot platform. The sample of this study were students of class IX.12 SMA Negeri 5 Makassar totalling 38 students. The instruments used in this study included observation sheets of teacher and student activities, as well as student writing assignments. Data were collected at each stage of the research through tests, observations, and documentation. The data obtained were analysed using qualitative and quantitative approaches. The results of the research in cycle 1 were only 18.4%, namely 7 out of 38 students included in the complete category with a score of 75 and as many as 81.6% or 31 out of 38 students included in the incomplete category. Whereas in cycle II, the percentage of students and the percentage of students who were not complete decreased to 11 students or 19.5% while the percentage of students who were complete increased by 68.9%. This shows that the use of Kahoot gamification succeeded in creating a more interactive, competitive, and fun learning atmosphere. So that it can increase student involvement in learning to write argumentation text.